Molecular Evolution of Auxin-Mediated Root Initiation in Plants. (5th April 2020) - Yu, Jie; Zhang, Yuyun; Liu, Wu; Wang, Hua; Wen, Shaoting; Zhang, Yijing; Xu, Lin
Abstract: The root originated independently in euphyllophytes (ferns and seed plants) and lycophytes; however, the molecular evolutionary route of root initiation remains elusive. By analyses of the fern Ceratopteris richardii and seed plants, here we show that the molecular pathway involving auxin, intermediate-clade WUSCHEL-RELATED HOMEOBOX (IC- WOX ) genes, and WUSCHEL-clade WOX (WC- WOX ) genes could be conserved in root initiation. We propose that the "auxin>IC- WOX >WC- WOX " module in root initiation might have arisen in the common ancestor of euphyllophytes during the second origin of roots, and that this module has further developed during the evolution of different root types in ferns and seed plants.